Evaluación del control del caracol (Helix Aspersa) con cloruro de sodio en forma líquida y sólida en el cultivo de tuna (Opuntia Ficus-Indica) del Campus Salache, cantón Latacunga provincia de Cotopaxi. - Monge Laverde, Anderson Javier (2023)
This research work was carried out at the Salache Experimental Center (CEASA), with the topic "Evaluation of snail (Helix aspersa) control with sodium chloride in liquid and solid form in the cultivation of prickly pear (Opuntia ficus-indica)" to evaluate the control of the snail with sodium chloride in liquid and solid form in the cultivation of prickly pear (Opuntia ficus-indica), the objective is to determine the incidence of the snail on prickly pear, and also to determine which form of sodium chloride application was better to combat the snail (Helix aspersa) in the prickly pear crop (Opuntia ficus-indica); and to evaluate the best application time of sodium chloride on prickly pear (Opuntia ficus-indica). A completely randomized block design (CRBD) with six treatments and three replications was used to achieve these objectives, giving a total of 18 experimental units. The results of the research determined that the best treatment was L1A3, which corresponds to sodium chloride in liquid form at 45 days; this was followed by treatment L1A2, which is sodium chloride in liquid form at 30 days, meaning that sodium chloride in liquid form was the most effective in controlling the snail in the prickly pear (Opuntia ficus-indica) crop. Finally, treatment S1A1, sodium chloride in solid form, was the least effective treatment in killing snails after 15 days.